2014
DOI: 10.1371/journal.pone.0087930
|View full text |Cite
|
Sign up to set email alerts
|

OPN and αvβ3 Expression are Predictors of Disease Severity and Worse Prognosis in Hepatocellular Carcinoma

Abstract: Expressions of OPN and αvβ3 are associated with a poor prognosis in many malignancies. However, their relationship in hepatocellular carcinoma remains unclear. We systematically collected hepatocellular carcinoma tissue samples from 305 patients over 3 years, and analyzed the status of OPN and αvβ3 in hepatocellular carcinoma and correlate expression with patient disease status and survival outcome. Our study results indicated that OPN and αvβ3 are expressed at significantly higher rates in hepatocellular carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Recent findings from immunohistochemical studies report integrin α v β 3 expression in 77 % of investigated HCC specimens whereas expression was detectable only in 22 % of normal liver tissue [13]. Patients with detectable integrin α v β 3 expression had a significantly worse survival, indicating a prognostic role of this integrin in patients with HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings from immunohistochemical studies report integrin α v β 3 expression in 77 % of investigated HCC specimens whereas expression was detectable only in 22 % of normal liver tissue [13]. Patients with detectable integrin α v β 3 expression had a significantly worse survival, indicating a prognostic role of this integrin in patients with HCC.…”
Section: Introductionmentioning
confidence: 99%
“…In prostate cancer, CCN3 is a potential therapeutic target for prevention of bone metastasis via inhibition of the FAK/Akt/p38/NF-κB signaling pathway 14 . Since αvβ3 integrin is the receptor for CCN3, it is interesting to note that patients with high expression of αvβ3 also had significantly shorter survival 15 . However, the precise physiological function and mechanism of action of CCN3 in HCC malignancy remain vague 4 .…”
Section: Discussionmentioning
confidence: 99%
“…5h). Prior work demonstrated that αvβ3 integrin expression is associated with tumor size, invasion, and metastasis of HCC, and that antisense gene transfections of αv and β3 integrin reduced proliferation in HEPG2 cells 40,41 . Our results suggest that increased degradation of integrins by LYTACs can result in significantly enhanced functional effects compared to the parent binder alone.…”
Section: Peptide-based Galnac-lytacs Degrade Integrins and Induce Antmentioning
confidence: 99%